Factors influencing insulin acceptance among type 2 diabetes mellitus patients in a primary care clinic: A qualitative exploration - Abu Hassan H.; Tohid H.; Mohd Amin R.; Long Bidin M.B.; Muthupalaniappen L.; Omar K. (2024)
Indexed by WOS/ Scopus